Genetic Improvement of Local Chickens by Crossing with the Label Rouge (T55*SA51): Carcass Characteristic, Organoleptic Qualities and Heterosis Effects - Youssao, I.A.K.; Senou, M.; Dahouda, M.; Kpodekon, M.T.; Djenontin, J.; Idrissou, N-D.; Bonou, G.A.; Tougan, U.P.; Ahounou, S.; Assogba, H.M.; Bankole, E.; Rognon, X.; et al. (International Journal of Poultry Science, 2009)
The aim of this study was to evaluate the carcass characteristic and the organoleptic qualities of Label Rouge, North and South Local Chicken and their crossbreed MnFl (females Label Rouge x males of North ecotype), MlFn (North females ecotype x males Label Rouge) and MsFl (Label Rouge females x males of the South ecotype). This study was carried out on the Experimentation Farm of the Polytechnic School of Abomey-Calavi, from August 2007 to may 2008. Ten chicken of each genotype were slaughtered at 24 weeks age. The local chickens of the North ecotype had a live weight at the slaughter significantly higher than that of the Southern ecotype and lower compared to the cross and the Label Rouge; the same tendency was observed for the noble carcass cuts. The carcass yield was similar for the six genetic types. The meats of Label Rouge chickens, the local chickens and the Cross MsFl were less tender (p<0.05) than those of North chickens and the Cross containing the “North blood” (MnFl and MlFn). No significant differences were observed in other hand on the juiciness and the flavor for the six genetic types. For each type of crossing, the heterosis effect of the live weight, the hot carcass weight and the wet carcass weight had a close values. In general, the different heterosis rates of the crossing male of North ecotype x female Label was superior than those of the other crossings.